Examining the Influence of Organisational Culture on Employee Retention in Telecommunications Industry, Lagos State, Nigeria - Omokhabi, Abiola Adiat; Fajimi, Babatunde Ayoola (NIU Journal of Humanities, 2023)
This study examined the influence of organisational culture on employee retention in telecommunications industry, Lagos State. The study used descriptive survey design. The sample size for the study comprised 71 respondents selected using a combination of convenience and purposive sampling techniques because they are subject experts and easily accessible in the human resources management community. The instrument was subjected to face and content validity and the Cronbach’s alpha co-efficient r-value of = 0.81 showed good internal consistency after the pilot study. The null hypothesis was rejected because the study revealed a strong positive significant relationship between organisational culture and employee retention at (r = 0.629, p = 0.00) in telecommunications industry, Lagos State. The level of awareness of the influence organisational culture on employee retention in the telecommunications industry, Lagos State was moderately significant in areas of core values, capacity development and change management, and employee engagement and productivity. There was no low significance, however, in awareness of strategic direction and intent as well as team orientation as components of organisational culture. The study recommended that organisations should increase their investment in organisational learning to provide training for employees to enhance their wellness and work life balance.  Keywords: Organisational Culture, Employee Retention, Employee Turnover, Workforce, Telecommunications Industry